2006
DOI: 10.1007/bf03325906
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exo-polysaccharides producing bacterial inoculation on growth of roots of wheat (Triticum aestivum L.) plants grown in a salt-affected soil

Abstract: Effect of soil salinity on physico-chemical and biological properties renders the salt-affected soils unsuitable for soil microbial processes and growth of the crop plants. Soil aggregation around roots of the plants is a function of the bacterial exo-polysaccharides (EPS), however, such a role of the EPS-producing bacteria in the saline environments has rarely been investigated. Pot experiments were conducted to observe the effects of inoculating six strains of EPS-producing bacteria on growth of primary (sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Similar results were obtained for wheat plants inoculated with either Azotobacter or Azospirillum (Ashraf et al, 2006). This significant increase in root adhering soil mass around the roots of rice plants inoculated with Azotobacter isolate AzRDM2 could be the result of either an increase in soil adhesion to roots or a higher soil aggregate stability around roots, or both.…”
Section: Resultssupporting
confidence: 81%
“…Similar results were obtained for wheat plants inoculated with either Azotobacter or Azospirillum (Ashraf et al, 2006). This significant increase in root adhering soil mass around the roots of rice plants inoculated with Azotobacter isolate AzRDM2 could be the result of either an increase in soil adhesion to roots or a higher soil aggregate stability around roots, or both.…”
Section: Resultssupporting
confidence: 81%
“…The obtained results indicate that the beneficial effects of inoculation are more pronounced for the average 100-seed weight and seed yield (ha −1 ) in plants grown in saline soil than those grown in non-saline soil. Similarly, Ashraf et al [35] concluded that the inoculation of EPS-producing bacteria is a valuable tool for ameliorating and increasing crop productivity under salinity stress. In this respect, Qurashi and Sabri [36] reported that inoculation with EPS-producing bacteria at a higher salt stress up to 100 mM increased soil aggregation, which was more pronounced around roots, while aggregates formed by exopolysaccharides favored plant growth under salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, the P, K and N concentrations were increased in lettuce plants; in contrast, Na + was decreased. Some observations revealed that the capacity of bacteria to mitigate salt stress is due to the production of polysaccharides binding Na + in the root zone (Ashraf et al 2006 ;Awad et al 2012 ). Sarathambal and Ilamurugu ( 2013 ) showed the detailed PGP-features of some salt-tolerant diazotrophic PGPR, which were used to restore growth of paddy under saline conditions.…”
Section: Minerals Uptake Nitrogen Fixation Siderophores Productionmentioning
confidence: 97%